Assessing the Role of Logistics Vehicles in Traffic Congestion and Air Pollution: Policy Implications from Surabaya’s CBD - Wasil, Mohammad; Pasa, Inda Tri; Prayitno, Hadi; Slamet, Asep Gunawan; Olfebri (Indonesian Scientific Publication, 2024)
Urban freight transport is essential for sustaining city economies, yet its unmanaged growth poses serious risks to mobility and environmental health. This study aims to evaluate the contribution of logistics vehicle operations to traffic congestion and air pollution in Surabaya’s central business district (CBD). Using a qualitative case study approach, data were collected through interviews, field observations, and secondary documentation. Results show that logistics vehicles account for 18–23% of peak-hour traffic, leading to 20–30% longer travel times, while air quality measurements recorded PM₂.₅ levels exceeding WHO thresholds, especially during logistics peak periods. These impacts are largely driven by the absence of delivery time restrictions, outdated vehicle standards, and insufficient infrastructure. Unlike global cities that implement structured freight policies, Surabaya lacks urban consolidation centers, low-emission zones, and delivery scheduling mechanisms, resulting in overlapping freight–commuter flows and heightened emissions. Findings provide evidence-based insights for implementing time-window regulations, low-emission zones, and consolidation hubs in rapidly urbanizing cities. This study contributes to urban freight literature by highlighting the compounded effects of fragmented delivery practices and outdated fleets in a Southeast Asian secondary city, offering a framework for data-driven policy reforms toward sustainable logistics.